Key technologies and research development of CMOS image sensors - Bin Luo; Fuxing Yang; Lei Yan (2010 Second IITA International Conference on Geoscience and Remote Sensing, 2010)
CMOS sensor has achieved monolithic imaging, the photoelectric imaging circuit of CMOS image sensor is integrated on a chip, this is an effective method of reducing the size and power consumption of the imaging system. With the development of manufacture technology, we have resolved the two bottleneck problem: sensor structure and sensor noise, which restricts the image quality of CMOS image sensor, and the image quality of CMOS sensor is close to or even reach the level of CCD sensor, so some CMOS image sensors are applied in certain high resolution imaging fields, especially we are all developing small satellite technology now, CMOS image sensor is ideal for space and remote sensing imaging, which requires the smaller system size, lower system power and lighter system weight, so CMOS image sensor has a very broad application prospects.